Arthroscopic suture-tape internal bracing is safe as arthroscopic modified Brostrom repair in the treatment of chronic ankle instability - IRGIT, KAAN SÜLEYMAN (SPRINGER, 2020)
Purpose The aim of the study was to compare the intermediate-term clinical outcomes between lateral ligaments augmentation using suture-tape and modified Brostrom repair in a selected cohort of patients. The hypothesis of the presented study is that suture-tape augmentation technique has comparable clinical and radiological outcomes with arthroscopic Brostrom repair technique. Methods Sixty-one consecutive patients with chronic ankle instability were operated between 2012 and 2016 randomized to 2 groups. First group was composed of 31 patients whom were operated using an arthroscopic Brostrom repair technique (ABR) and second group was composed of 30 Patients whom were operated using arthroscopic lateral ligaments augmentation using suture-tape internal bracing (AST). At the end of total follow-up time, all patients were evaluated clinically using the Foot and Ankle Outcome Score (FAOS) and Foot and Ankle Ability Measure (FAAM). Radiological evaluation was performed using anterior drawer and varus stress radiographs with standard Telos device in 150 N. Talar tilt angles and anterior talar translation were measured both preoperatively, 1 year postoperatively and at the final follow-up. Results Preoperative total FAOS scores for ABR and AST groups were 66.2 +/- 12 and 67.1 +/- 11, respectively. Postoperative Total FAOS scores for ABR and AST groups were 90.6 +/- 5.2 and 91.5 +/- 7.7, respectively. There was no statistical difference in between 2 groups both pre- and postoperatively (n.s). According to FAAM, sports activity scores of ABR and AST groups were 84.9 +/- 14 and 90.4 +/- 12 at the final follow-up, which showed that AST group was significantly superior (p = 0.02). There were no significant differences in preoperative and postoperative stress radiographs between the two groups. Mean operation time for AST and ABR groups were 35.2 min and 48.6 min, respectively, which shows statistically significantly difference (p < 0.05). There was no significant difference in recurrence rate of instability between to operation techniques (n.s). Conclusions Arthroscopic lateral ligament augmentation using suture tape shows comparable clinical outcomes to arthroscopic Brostrom repair in the treatment of chronic ankle instability at intermediate-term follow-up time. Arthroscopic lateral ligament augmentation using suture tape has a significant superiority in the terms of less operation time and no need for cast or brace immediate after surgery which allows early rehabilitation. It also has a significant superiority in the terms of FAAM scores at sports activity. However, there was no difference during daily life.
Keywords: Chronic; Ankle; Lateral instability; Internal bracing; Brostrom; Reconstruction; ANTERIOR TALOFIBULAR LIGAMENT; RECONSTRUCTION; AUGMENTATION; FOOT